Performance of factor IX extended half‐life product measurements in external quality control assessment programs. (10th June 2020) - Nederlof, Angelique; Kitchen, Steve; Meijer, Piet; Cnossen, Marjon; Ali Pour, Nae; Kershaw, Geoffrey; Jennings, Ian; Walker, Isobel; de Maat, Moniek P. M.
Abstract: Background: Patients with hemophilia B are increasingly treated with extended half‐life (EHL) factor IX (FIX) concentrates. For the laboratory, introduction of these EHL concentrates presents a major challenge. To understand the variation in FIX activity levels, all available diagnostic assays need to be directly compared. Methods: The ECAT, UKNEQAS, and RCPAQAP have collaboratively performed a global survey to evaluate the quality of FIX measurements using FIX deficient plasma samples spiked with recombinant FIX (rFIX), rFIXFP, rFIXFc, and N9‐GP to levels at typical FIX trough (6 IU/dL) and peak levels (60 IU/dL). Participants were asked to use their routine protocols, using one‐stage assays (OSA) or chromogenic assays (CA). Results: In samples spiked with 6 IU/dL product, median (25%‐75% range) FIX activity levels (OSA), were 8.0 IU/dL (7.0‐9.2) for rFIX, 6.0 IU/dL (4.0‐7.1) for rFIXFP, 6.6 IU/dL (5.5‐8.0) for rFIXFc, and 4.9 IU/dL (3.5‐8.4) for N9‐GP. In samples spiked with 60 IU/dL, FIX activity levels measured (using OSA) was 63.0 IU/dL (59.9‐67.0) for rFIX, 42.5 IU/dL (28.2‐47.0) for rFIXFP, 50.0 IU/dL (45.0‐55.0) for rFIXFc, and 34.0 IU/dL (24.8‐67.5) for N9‐GP. Considerable differences were observed between reagents for all samples. With CA, there was also quite some variation, but no differences between reagents. Conclusion: Large variation is observed in the measurement of FIX activity levels after administration of rFIX and EHL FIX products. For N9‐GP, most silica‐based assays show especially high levels. It is essential to standardize and improve reliability of measurements of these concentrates as diagnosis and treatment monitoring is based on these results.